Policy Based Management for Internet Communities - FEENEY, KEVIN; LEWIS, DAVID; WADE, VINCENT PATRICK (IEEE Press, 2004)
Policy Based Management (PBM) is a research topic that has been driven by the tremendous complexity inherent in the administration and management of present-day networking and telecommunications systems and services. The increasingly diverse organisational forms of modern industry represent a significant component of this complexity. Internet communities offer extreme examples of organisational diversity, since they often lack any central authority and many subsections operate with almost complete autonomy. This paper argues that PBM systems offer great potential in this domain due to the complexity of management arrangements. However, since these communities lack any single trusted administrative hierarchy, a centralised solution to policy engineering and management is not possible. This paper proposes an approach to modelling communities for PBM systems. This approach focuses on the concept of communities within a hierarchy of authority as the fundamental unit of organisational analysis. As such, the model reflects the distribution of authority in the real-world community, the resulting policies reflect the community's operational needs and contracts between the various groups and individuals that make up the community. Policy conflicts are used to identify organisational conflicts that must be resolved. In order to illustrate and validate these concepts, the paper presents a conceptual architecture and case study based on the secure management of an open publishing network.
PUBLISHED
Keywords: Computer Science